Assessment of fallen equine data in France and their usefulness for epidemiological investigations. (February 2016) - Tapprest, Jackie; Borey, Marion; Dornier, Xavier; Morignat, Eric; Calavas, Didier; Hendrikx, Pascal; Ferry, Bénédicte; Sala, Carole
Abstract: Quantitative information about equine mortality is relatively scarce, yet it could be of great value for epidemiology purposes. Several European projects based on the exploitation of data from rendering plants have been developed to improve livestock surveillance. Similar data are available for equines in France but have never been studied to date. The objective of this research was to evaluate the potential of the French Ministry of Agriculture's Fallen Stock Data Interchange (FSDI) database to provide quantitative mortality information on the French equine population. The quality of FSDI equine data from 2011 to 2014 was assessed using complementary data registered in the French equine census database, SIRE. Despite a perfectible quality, the FSDI database proved to be a valuable source for studying the basal patterns of mortality over time in the French equine population as illustrated by the spatial representation of the number of deaths. However, improvements in the FSDI database are needed, in particular regarding the registration of animal identification numbers, in order to detail equine mortality for epidemiology purposes. Highlights: Fallen equine data is a valuable source of information about equine mortality. Fallen equine data provided a description of the spatial variations in equine deaths. Fallen equine data could allow temporal modeling of equine mortality figures. Fallen equine data could be used for epidemiology purposes.